Editorial Board and Guidelines for the Authors, EDUCARE Journal, Issue of August 2016. - EDUCARE, Editor Journal (EDUCARE, 2016)
EDUCARE journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the educational studies in general and its various aspects. Analysis will be practical and rigorous in nature. The EDUCARE journal, with Print ISSN 1979-7877, was firstly published on 17 August 2008, in the context to commemorate the Independence Day in Indonesia. Since issues of February 2009 to February 2016, the EDUCARE journal was organized by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE journal is published twice a year, i.e. every August and February.Bandung, West Java, Indonesia: August 30, 2016.Assoc. Prof. Dr. Ismail AliHead of Experts Board of ASPENSI in Bandung; and a Senior Lecturer at the Department of History UMS (Malaysia University of Sabah) in Kota Kinabalu, Sabah, Malaysia.Â